Duration of untreated prodromal symptoms in a Chinese sample at a high risk for psychosis: demographic, clinical, and outcome. Issue 8 (27th November 2017) - Zhang, TianHong; Xu, LiHua; Tang, YingYing; Cui, HuiRu; Wei, YanYan; Wang, JunJie; Tang, XiaoChen; Li, ChunBo; Wang, JiJun
Abstract: Background: The duration of untreated psychosis (DUP) has been widely studied. However, for individuals with attenuated psychosis syndrome (APS), it is unclear whether the duration of untreated prodromal symptoms (DUPrS) also has a negative effect on the progression of psychosis. Our aim was to identify demographic and clinical factors contributing to the DUPrS in a large sample of individuals with APS, and to evaluate the association between DUPrS and the conversion to psychosis. Method: A sample of 391 individuals with APS, who were identified through a structured interview for prodromal syndromes, were included in this study, of whom a total of 334 patients had completed at least a 1-year clinical follow-up. A total of 57 individuals had converted to psychosis. Results: The average DUPrS was 4.8 months for the whole sample. Individuals with a longer DUPrS were likely to be men, non-local residents, with abnormal thought symptoms, a higher severity level of negative symptoms, the lower severity level of general symptoms, and lower level of general function before the onset of attenuated positive symptoms. A DUPrS of less than 2 months, or more than 6 months, lowered the risk for conversion to psychosis. Conclusions: Our data suggested that the association between the DUPrS and outcome in individuals with APS were likely to be different, which is either long or short DUPrS was not related to future psychosis onset. Individuals with APS were more likely to have a group of features associated with a longer DUPrS.